Soil susceptibility analysis to erosive processes of the Parque Natural Municipal Corredores de Biodiversidade (PNMCBio) OF Sorocaba (SP) - Simonetti, Vanessa Cezar [UNESP]; Da Cunha e Silva, Darllan Collins; De Oliveira, Renan Angrizani; Sabonaro, Débora Zumkeller; Rosa, André Henrique [UNESP] (Universidade Federal do Paraná, 2018)
Soils are of fundamental importance for humanity, however anthropic activities have been exerting strong pressure on this resource, triggering erosive processes. The present study aimed to identify the area’s most susceptible to laminar erosion from the characterization of soil physical-hydric attributes in two distinct zones of the Parque Natural Municipal Corredores de Biodiversidade (PNMCBio) located in the city of Sorocaba (SP). Soil samples were extracted in the Intangible Zone (ZI) and Recovery Zone (ZR) in depth 0-20 cm, the zones were prioritized for the study by the distinct characteristics and the depth is the most susceptible to erosion. In each zone, analyzes of particle size, moisture (volumetric and gravimetric), apparent density and total porosity were performed, and the soil erodibility factor (K) was calculated indirectly by Bouyoucos expression from the data obtained by the particle size analysis. These results were interpolated to analyze the spatial distribution of these attributes in the study area. In both areas, the soil was classified as medium erodibility, therefore, the maintenance of the park as a conservation unit ensures that the anthropic management in this area is sustainable and does not trigger any erosive process. The present study makes an important contribution to the characterization of the soil physical-hydric attributes in the PNMCBio, making possible to evaluate in a spatialized way the area’s most susceptible to laminar erosion and provide support for management and decision-making by the agencies responsible for conservation.
Análise da suscetibilidade do solo a processos erosivos do Parque Natural Municipal Corredores de Biodiversidade (PNMCBIO) DE Sorocaba (SP)
Keywords: Conservation units; Hydric erosion; Soil conservation; Soil erodibility